UPAYA MENINGKATKAN HASIL BELAJAR PAK MENGGUNAKAN MODEL ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION PADA SISWA KELAS VII-D SMP NEGERI 1 SIPOHOLON KABUPATEN TAPANULI UTARA TAHUN AJARAN 2021/2022 - RAHIMA TAMPUBOLON (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
ABSTRACT, This study aims to describe the increase in PAK learning outcomes by using the active learning model type of role reversal question in class VII-D students of SMP Negeri 1 Sipoholon, North Tapanuli Regency. This type of research is classroom action research. The research subjects were students of class VII-D SMP Negeri 1 Sipoholon, North Tapanuli Regency, totaling 36 students. Data collection methods in this study used tests, observation and documentation. Research instruments in the form of tests and observation sheets. The data analysis technique used is descriptive quantitative and qualitative. The indicator of the success of the action is marked by ≥75% of the number of students participating in the learning process who have obtained a value of ≥70. The results showed that there was an increase in PAK learning outcomes for class VII-D students of SMP Negeri 1 Sipoholon, North Tapanuli Regency after using the active learning model type of role reversal question in both cycle I and cycle II. In cycle I students who scored ≥70 experienced an increase of 25% and in cycle II experienced an increase of 28% to 97%.